Alternatives: Canada, the COVID-19 waiver, and trade fetishism. Issue 1 (2nd January 2022) - Fridell, Gavin
Abstract: Canada's resistance to the COVID-19 waiver of intellectual property rights at the World Trade Organization (WTO) for so long remains a conundrum given the Trudeau government's stated devotion to "progressive trade." This article summarizes Canada's global pandemic efforts, arguing that progressive trade in fact helps to explain its waiver stance. Progressive trade evokes trade liberalization as a simple, even magical "fetish" that realizes unconscious desires for disavowal, mastery, and foreclosure. Trade fetishism asserts itself against the waiver, revealing the limits of Canada's approach and the fantasies that animate it. This paper is part of the SPE Theme on the Political Economy of COVID-19.